A new instrument for root canal system finishing after chemomechanical preparation: XP-Endo Finisher - Nathália Ribeiro Valente; Juliana Zumpichiatti Paredes Oliveira; Ana Vitória Moura de Carvalho Valoura; Fernanda Hecksher; Edson Jorge Lima Moreira; Emmanuel João Nogueira Leal da Silva (Associação Brasileira de Odontologia, 2017)
Objective: the objective of this paper is to present a literature review on XP-endo Finisher, addressing the results of studies that evaluated this new endodontic instrument. Material and Methods: a search was undertaken in PubMed and Bireme databases between 2015 (when the instrument was launched to the market) and 2017 using the following descriptors: XP-endo Finisher. Results: eighteen papers were retrieved and divided into categories according to the type of evaluation: Removal of calcium hydroxide paste; Removal of triple antibiotic paste; Removal of filling material; Extrusion of sodium hypochlorite during instrumentation; Extrusion of dentin debris during instrumentation; Antimicrobial and antibiofilm action; and removal of smear layer and debris. Conclusion: according to the papers reviewed in this study, it may be concluded that XP-endo Finisher may have a positive impact on the endodontic treatment. This instrument showed promising results for intracanal medication removal; filling material removal during endodontic retreatment; smear layer and debris removal; enhance of the antimicrobial action of irrigants; and improvement of biofilm removal.